2010
DOI: 10.1007/s11240-010-9837-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NADPH oxidase-mediated H2O2 signaling in PB90-induced hypericin accumulation in Hypericum perforatum cells

Abstract: PB90 is a novel protein elicitor isolated from Phytophthora boehmeriae. Here, we report that treatment of PB90 stimulates hypericin production and hydrogen peroxide (H 2 O 2 ) generation in Hypericum perforatum L. cells and demonstrate that H 2 O 2 is essential for PB90-induced hypericin production. To further study the source of PB90-triggered H 2 O 2 , we have investigated activities of plasma membrane NADPH oxidase in Hypericum perforatum L. cells subjected to PB90 treatment. It is revealed that treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It has been well documented that the elicitor-induced secondary metabolite production is mediated by endogenous signalling pathways involving signal molecules such as nitric oxid, JA, SA and H 2 O 2 . In this view, fungal elicitors induced HYP production in H. perforatum cells through a JA dependent signalling pathway (Xu et al 2005) or NADPH oxidase-mediated H 2 O 2 signalling pathway (Xu et al 2011). It is still unclear whether elicitors acted on the same or distinct signalling pathways and further research is needed to better understand the effects of various elicitors on secondary metabolites partitioning in H. perforatum cell suspensions.…”
Section: Effects Of Fungal Elicitors On the Secondary Metabolism Chanmentioning
confidence: 99%
“…It has been well documented that the elicitor-induced secondary metabolite production is mediated by endogenous signalling pathways involving signal molecules such as nitric oxid, JA, SA and H 2 O 2 . In this view, fungal elicitors induced HYP production in H. perforatum cells through a JA dependent signalling pathway (Xu et al 2005) or NADPH oxidase-mediated H 2 O 2 signalling pathway (Xu et al 2011). It is still unclear whether elicitors acted on the same or distinct signalling pathways and further research is needed to better understand the effects of various elicitors on secondary metabolites partitioning in H. perforatum cell suspensions.…”
Section: Effects Of Fungal Elicitors On the Secondary Metabolism Chanmentioning
confidence: 99%
“…The production of ROS and H2O2 in plants also acts as a secondary messenger to signal subsequent defence reactions (Low and Merida 1996). The reactive oxygen intermediates, such as H2O2, generated by an oxidative burst are considered to be important signalling molecules in plants, and it has been reported that H2O2 is essential for PB90-induced hypericin production in H. perforatum cells (Xu et al 2011). High sucrose concentrations leads to an increased accumulation of phenols, flavonoids, chlorogenic acid, and total hypericin in root suspension cultures of H. perforatum, and it is thought that this might be due to the osmotic stress that is caused by increased sucrose concentrations (Cui et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A multitude of signaling factors have been reported to be connected to ABA responses and ABA has emerged as a core of the signaling network in plant defense responses . Recently, ABA has been reported to be involved in ozone‐induced Taxol production in Taxus chinensis cell cultures and puerarin production of Pueraria thomsnii suspension cells . However, unequivocal evidence for a causal relationship between ABA and elicitor‐induced catharanthine biosynthesis of C. roseus cell cultures is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that PB90 could trigger plant defense responses. Recently, we reported that treatment with PB90 efficiently induced camptothecin accumulation in Camptotheca acuminata cells and hypericin production in Hypericum perforatum cells, which suggested that PB90 might be a potential elicitor for improving secondary metabolite production of plant cell cultures.…”
Section: Introductionmentioning
confidence: 99%